POTENSI DAYA TARIK OBJEK WISATA AIR TERJUN DAIT DI DESA SEKENDAL KECAMATAN AIR BESAR KABUPATEN LANDAK - Yuvensius, Paulinus; Kartikawati, S M; Prayogo, Hari (Universitas Tanjungpura, 2017)
Potential and attraction of ecotourism on the waterfall in the village Sekendal Dait gives rise to the desire of the community to undertake the development of tourism. To that end, this study has several objectives, namely (a) know the potential of ecotourism resources in Sekendal Village, namely waterfalls Dait (b) know the motivation, participation and people's interest towards the development of ecotourism waterfall Dait, (c) Provide alternative package tours as well as provide feedback to the community as well as the District Tourism Office and Office related service Urchins to develop Attractions Dait waterfall in the village of Sekendal. Data retrieval community respondents and visitors is done with a questionnaire and interview methods later data processed by using the tabulator system. Furthermore, the data tabulated results were analyzed using analysis of ODTWA. The results of the research on the development potential of Attraction Attractions Waterfalls Dait namely the development potential of the tourist attraction of waterfall dait which can be done in the village of Sekendal is a form of ecotourism educative. The potential of ecotourism resources in the village of Sekendal that can be used as tourist attraction in the form of the landscape and culture of the community Sekendal. These include cultural mores in different rituals for the safety of visitors, visitors who visit the waterfall Dait average profession as a student/undergraduate student was about 17-25 years of age with the majority of visitors on motivations of domination for campingKeyword : Ecotourism, ODTWA, Society, Waterfall.